Oral Squamous Cell Carcinoma in Young Patients Show Higher Rates of EGFR Amplification: Implications for Novel Personalized Therapy - Satgunaseelan, Laveniya; Porazinski, Sean; Strbenac, Dario; Istadi, Aji; Willet, Cali; Chew, Tracy; Sadsad, Rosemarie; Palme, Carsten E.; Lee, Jenny H.; Boyer, Michael; Yang, Jean Y. H.; Clark, Jonathan R.; et al. (Frontiers in Oncology, 2021)
There is an increasing worldwide incidence of patients under 50-years of age presenting with oral squamous cell carcinoma (OSCC). The molecular mechanisms driving disease in this emerging cohort remain unclear, limiting impactful treatment options for these patients. To identify common clinically actionable targets in this cohort, we used whole genome and transcriptomic sequencing of OSCC patient samples from 26 individuals under 50-years of age. These molecular profiles were compared with those of OSCC patients over 50-years of age (n=11) available from TCGA. We show for the first time that a molecular signature comprising of EGFR amplification and increased EGFR RNA abundance is specific to the young subset of OSCC patients. Furthermore, through functional assays using patient tumor-derived cell lines, we reveal that this EGFR amplification results in increased activity of the EGFR pathway. Using a panel of clinically relevant EGFR inhibitors we determine that an EGFR-amplified patient-derived cell line is responsive to EGFR inhibition, suggesting EGFR amplification represents a valid therapeutic target in this subset of OSCC patients. In particular, we demonstrate sensitivity to the second-generation EGFR tyrosine kinase inhibitor afatinib, which offers a new and promising therapeutic avenue versus current EGFR-targeting approaches. We propose that testing for EGFR amplification could easily be integrated into current diagnostic workflows and such measures could lead to more personalized treatment approaches and improved outcomes for this younger cohort of OSCC patients.